Strengthening Religious Development Through Lailatul Ijtima' Guidelined By Amaliyah Nu In Rejecting Radicalism - Saiful Bahri; Imam Syafi’i (Journal of Social Science and Economics, 2022)
The trend of cases of intolerance and radicalism continues to increase from year to year, influenced by political contestations, lectures or speeches containing hate speech, as well as hateful uploads on social media (social media), the lack of aswaja lessons in schools makes students less understanding of moderate Islam which respect differences. The formulation of the problem in this study is 1) How is the religious development carried out at MDTA Nurul Ilmi Sumberjati Mojoanyar Mojokerto? 2) How are the activities of lailatul ijtima' guided by NU at MDTA Nurul Ilmi Sumberjati Mojoanyar Mojokerto? 3) What is the strategy to reject radicalism at MDTA Nurul Ilmi Sumberjati Mojoanyar Mojokerto? This research approach uses discrete qualitative because in this research it produces conclusions in the form of data that describes in detail, not data in the form of numbers, and this type of research is a case study, which is part of a qualitative method that wants to explore a particular case. in more depth by involving the collection of various sources of information. The results of this research are 1) The religious guidance carried out at MDTA Nurul Ilmi is different from other MDTA 2) Lailatul ijtima' is an NU program and is collaborated by MDTA Nurul Ilmi Sumberjati 3) The strategy carried out by MDTA Nurul Ilmi in rejecting radicalism by understand the teachings of Islam ASWAJA NU correctly.